Transgender Inclusivity in Iranian Shia Tradition: Rethinking Sex and Gender Dynamics - Tajer, Leyla H.; Hickson, Andy (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
The relationship between sex, gender, and sexual orientation—particularly within Islamic contexts—presents complex global challenges. In many Western societies, confusion between biological sex and socially constructed gender has led to identity conflicts. Lesbian, gay, and bisexual (LGB) identities are based on sexual orientation, while transgender identities focus on gender, often intersecting with diverse sexual preferences. This overlap complicates the understanding of gender dysphoria and creates tensions between transgender individuals and the broader LGB community. Iran offers a distinct approach by classifying transgender identity as a psychological condition, separate from LGB identities. This perspective underscores how cultural and psychological frameworks shape societal attitudes toward gender variance. By analyzing literature, official documents, and media, this study explores the evolution of LGB and transgender identities in Iran and the West. Despite differing cultural norms, both contexts often blur the boundaries between biology and culture, leading to persistent misconceptions and exclusion. The study highlights the need to question prevailing social norms and calls for further qualitative research, especially on the post-transition experiences of Iranian transgender individuals, to inform more inclusive and culturally aware global policies.